ANALISIS DAN PERANCANGAN SIKLUS PENDAPATAN BERBASIS CUSTOMER RELATIONSHIP MANAGEMENT UNTUK MENINGKATKAN LOYALITAS PELANGGAN PADA UD “MITRA BARU” DI MATARAM - Eka Cipta Adiputra; Adhicipta Raharja Wirawan (CALYPTRA, 2018)
This study aims to analyze and design Revenue cycle based on Customer Relationship Management at UD "Mitra Baru" located in Mataram, NTB. This research uses qualitative approach with UD "Mitra Baru". UD "Mitra Baru" is a business entity engaged in the distribution or as a distributor. The products distributed include biscuits, drinking water, and sachets. The main role of distributor activity is largely supported by the leading role of sales, manager, and administration. The analysis is based on the application of Customer Relationship Management, as well as the size of customer loyalty to UD "Mitra Baru", thus finding various issues related to earnings cycle. Problems are also known through interviews. Problems are supported by various policies that are implemented, among others: sanctions in the form of reprimands, communication via mobile phone, monitoring process, and recording on Customer Record Card. Problems include: database problems, product offerings, customer complaints, lack of online tools, mapping areas, lack of communication with outlets, and customer loyalty. The results of research on UD "Mitra Baru" is in the form of recommendations that can be used as a system design for increased loyalty. Recommendations include: Membership card, Customer Service Party, Website or online system, database addition, and improvement of Control. These recommendations are appropriate for the development of UD "Mitra Baru" business. This shows that a Customer Relationship Management is very important to improve customer loyalty. The main objective of the internal party is to sustain the business in terms of income continues to grow primarily through customer relations.